Grain Sorghum Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2008)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in northeastern Kansas.
MF573_2008_10
Keywords: MF573; Economics; Crops; MF